Edukasi Robotika untuk Siswa SMP Menumbuhkan Minat dan Kreativitas di Bidang STEM - Ribut Julianto (Jurnal Dedikasi untuk Negeri, 2025)
Technological advancement in the era of the Fourth Industrial Revolution demands that the younger generation acquire 21st-century skills, particularly in science, technology, engineering, and mathematics (STEM). However, technological literacy at the junior high school level, especially in rural areas such as Jatiagung District, remains relatively low. This community service program aims to introduce basic robotics to junior high school students as an effort to foster interest and creativity in the STEM field. The program was implemented in six schools with a total of 120 participants, using lectures, demonstrations, and hands-on project-based activities. The results of pre-test and post-test assessments showed an average increase of 62.1% in students' knowledge. Additionally, students demonstrated high enthusiasm, strong teamwork skills, and successfully created simple and creative robotic projects. The involvement of teachers in this activity also supported the sustainability of the program at the partner schools. Robotics education has proven to be an effective approach for enhancing students’ technological literacy and supporting the development of education that is relevant to the challenges of the digital era.